EVALUASI KUALITAS ESTETIKA FASADE BANGUNAN DENGAN PENDEKATAN BIRKHOFF AESTHETIC MEASURE - Donna Mulyo Saputro; Baritoadi Buldan Rayaganda Rito (Universitas Islam Indonesia, 2020)
Planning a property building must be unique and attractive in order to be accepted by consumers. The attractiveness of a building design can increase the purchasing power of consumers towards property units. One of the efforts in increasing the attractiveness of buildings is by increasing the aesthetic value of a building's face (building facade). From the research data that has been done, the influence of building facade design on consumer buying interest is ranked second after the location of the unit. To determine the level of aesthetic quality of a building facade, it can be calculated using the Birkhoff Measure method. The method is carried out by providing aspects of the assessment of respondents, then respondents will provide a quantitative assessment of the aspects assessed. The value of this aspect will be calculated using an existing formula, the result will be the quality value of a building facade. From these results it will be known that the facade design has a high aesthetic value that can be accepted by consumers in general. Calculations using the Birkhoff Measure method need to be done in order to minimize failures in the design of the building facade, so that the design of the building offered can add to the consumer's purchasing power to the unit property.